2019
DOI: 10.1039/c9ra00227h
|View full text |Cite
|
Sign up to set email alerts
|

Optimized synthesis of novel hydrogel for the adsorption of copper and cobalt ions in wastewater

Abstract: Metal ions in wastewater endanger the environment and even human life. In this study, an optimized method was used to synthesize an excellent hydrogel to treat these metal ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…There has also been work carried out on cobalt(II) adsorption by using Si/Ti-based, amino-functionalized hybrids, 15 graphite, activated carbon, 16 or hydrogels. 17 These investigations highlight the present interest in the development of new materials as sorbents for cobalt(II).…”
Section: ■ Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…There has also been work carried out on cobalt(II) adsorption by using Si/Ti-based, amino-functionalized hybrids, 15 graphite, activated carbon, 16 or hydrogels. 17 These investigations highlight the present interest in the development of new materials as sorbents for cobalt(II).…”
Section: ■ Introductionmentioning
confidence: 92%
“…Zhuang and Wang obtained a maximum sorption capacity of 15.24 mg/g using a magnetic graphene oxide/chitosan composite as a sorbent. There has also been work carried out on cobalt­(II) adsorption by using Si/Ti-based, amino-functionalized hybrids, graphite, activated carbon, or hydrogels . These investigations highlight the present interest in the development of new materials as sorbents for cobalt­(II).…”
Section: Introductionmentioning
confidence: 94%
“…The results suggested that the active sites on the hydrogel surface are homogenously distributed. The adsorption of Pb(II) ions by PC-PAAc/GA hydrogel is a chemical adsorption process [64]. It is also noted that PC-PAAc/GA hydrogel contains many hydroxyl and carboxylic groups that can attract and coordinate with Pb (II) cations.…”
Section: Adsorption Studymentioning
confidence: 99%
“…The thermodynamics of the adsorption of metal ions using the Cr-MOF/AC composite was investigated by varying the temperature in the range of 298–318 K under the optimum conditions. The thermodynamic parameters including Gibbs free energy (Δ G 0 ), enthalpy (Δ H 0 ), and entropy (Δ S 0 ) were obtained using the following equations and shown in Table : where R (8.314 J/mol.K) and T (K) are the universal gas constant and the temperature of the solution, respectively. The results have shown that the values Δ G 0 were negative for both the Pb­(II) and Co­(II) ions and decreased with the increase of temperature, suggesting the spontaneous nature of the adsorption.…”
Section: Resultsmentioning
confidence: 99%